A Modified Posterolateral Approach for Radiofrequency Denervation of the Medial Branch of the Cervical Segmental Nerve in Cervical Facet Joint Pain Based on Anatomical Considerations. Issue 5 (13th October 2016) - van Eerd, Maarten; Lataster, Arno; Sommer, Micha; Patijn, Jacob; van Kleef, Maarten
Abstract: The cervical facet joints, also called the zygapophyseal joints, are a potential source of neck pain (cervical facet joint pain). The cervical facet joints are innervated by the cervical medial branches (CMBs) of the cervical segmental nerves. Cervical facet joint pain has been shown to respond to multisegmental radiofrequency denervation of the cervical medial branches. This procedure is performed under fluoroscopic guidance. Currently, three approaches are described and used. Those three techniques of radiofrequency treatment of the CMBs, classified on the base of the needle trajectory toward the anatomical planes, are as follows: the posterolateral technique, the posterior technique, and the lateral technique. We describe the three techniques with their advantages and disadvantages. Anatomical studies providing a topographic anatomy of the course of the CMBs are reviewed. We developed a novel approach based on the observed strengths and weaknesses of the three currently used approaches and based on recent anatomical findings. With this fluoroscopic‐guided approach, there is always bone (the facet column) in front of the needle, which makes it safer, and the insertion point is easier to determine without the risk of positioning the radiofrequency needle too dorsally.